Pemanfaatan Kompleks Polielektrolit sebagai Matriks untuk Immobilisasi Urease dan Aplikasinya sebagai Membran Biosensor Pemonitoran Hg(II) - Dhony Hermanto; Mudasir Mudasir; Dwi Siswanta; Bambang Kuswandi (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2019)
The preparation of polyelectrolyte complex (PEC) as supporting material of urease immobilisation for Hg(II) biosensor has done. PEC membrane can be prepared by mixing hydrosol alginate and chitosan hydrosol with 1: 1 ratio at pH of 5.28 approximately. The optimum conditions and characteristics of biosensor was determined. The formed alginate–chitosan PEC membrane was confirmed by using FTIR spectroscopy and SEM analysis. The results shoed that PEC of alginate-chitosan was formed and the proposed biosensor is an excellent platform for sensitive detection of Hg (II).